The Evaluation оf Potential Threat оf Animal’s Coronaviruses аs Human’s Patogens - T. E. Sizikova; V. N. Lebedev; S. V. Borisevich (Вестник войск РХБ защиты, 2021)
The introduction of SARS-CoV-2 coronavirus from a natural reservoir into the human population subsequently caused the COVID-19 pandemic, that had a huge impact on all spheres of human activity dramatically increased interest in this group of viruses. Given that such an introduction of the coronavirus was already the third in a row in 21 century (after outbreaks caused by SARS-CoV and MERS-CoV viruses), there are quite good reasons to fear the appearance of new diseases, the etiological agents of which will be representatives of the Coronaviridae family in the future. The purpose of this review is to assess the potential risk of coronaviruses of animals as possible human pathogens. When preparing the review, the following data were used: data published in leading foreign journals as well as in Internet sources that address some aspects of the COVID-19 pandemic. The following main aspects of this problem are considered: a spontaneous formation during the evolution of animal coronaviruses, highly pathogenic to humans; a possibility of transmission of human coronavirus to animals, its genetic interaction with the coronavirus, the owner of which is this animal, the acquisition of viral progeny, a set of new properties and reverse transmission from animal to man a pathogen that may have increased pathogenicity. Animal coronaviruses are considered by belonging to a certain taxonomic group of their natural hosts. The main focus is on bat coronaviruses (as a reservoir of SARS-CoV, MERS-CoV and SARS-CoV-2 viruses), as well as avian coronaviruses, due to the potential ability of these animals to become vectors of spread of new emergent diseases and the coronaviruses of carnivores, due to the established during the COVID-19 pandemic fact of transmission of the SARS-CoV-2 virus from man to mink and from mink to man. Studying the features of molecular evolution it will help you better understand the mechanisms of occurrence and adaptation to humans pathogens of emergent viral diseases.